Pengembangan Sistem Manajemen Kelas Berbasis Website Sebagai Solusi Pelaporan Pembelajaran Digital - Lalu, Widi Natasya; Novian, Dian; Muthia, Muthia; Latief, Mukhlisulfatih; Padiku, Indhitya R; Dwinanto, Arif (Universitas Negeri Gorontalo, 2024)
The use of information technology in the world of education has made a major contribution to increasing the efficiency, accuracy and transparency of the educational process. The role of the homeroom teacher is very important for student development. The process of reporting assignment data, grades, absence recaps, student report cards to parents, which still rely on conventional reporting, and conveyed via correspondence or WhatsApp messages, is a problem that must be addressed. The aim of this research is to design a website-based classroom management system; Achievement of a classroom management system by testing usability and suitability as well as testing the practicality of a system that is suitable for use. The system development method used in this research is the waterfall method. The respondents of this research are teachers, students and parents. The instrument used in the research is a questionnaire and testing in this research includes functional suitability to determine whether the system is functioning well, usability or suitability to determine whether the system is suitable for use and practicality testing to determine the efficiency of the system. The results of the functional suitability test show that the system is as expected, and based on the results of the system suitability test by the user, results were obtained with a percentage score of 84.66% from 6 teachers, including the very suitable category. Then the results of the practicality test by system user respondents were 92.47% of the results of student responses and 90.53% of the results of parent responses. So the Website-Based Class Management System is suitable for use.